Examination of hydrodynamic behavior of wind deflectors in the normal inner temperature with the point of more efficiency (Case study: Bwhsa Köppen climate classification of Kashan City) - Mohammadali Karbasforoushha (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
One of the ways to achieve a building with higher energy efficiency and an efficient system is to use local architectural experiences. In the meantime, a wind deflector is one of the elements used in the past to create comfort. In the Bwhsa Köppen climate classification of Kashan City, they used to move and cool the air in the building. This study investigates the interior of these settlements in this climate to aim to reach greater efficiency of this element by CFD software, Energy Plus, and Open Studio with a descriptive-analytical method and then analyzes the results. A comparison of the results of the analysis of wind speed in wind turbines and how the wind is oriented in the interior is shown. Due to the low thermal mass of the wind deflector walls compared to the room, the temperature fluctuation is always higher than in the room. The main factors in temperature drop are proportionality of dimensions-air inlet valve to the windshield, water temperature, measurements, and height of the windshield column. Finally, to reduce the room temperature further, the priority is to use a spray windshield over windshield wipers. Especially windshields with water spray in which most of the room has a temperature of 25 degrees Celsius and are in Kashan city's thermal comfort range.